FAKE NEWS DIGITALES Y SU EFECTO EN LA COMUNICACIÓN CIUDADANA DEL CANTÓN EL EMPALME SECTOR SAN FELIPE. AÑO 2022. - Moreira Avila, Nayely Maoly (2022)
The objective of this research is to identify the consequences of the exposure of digital fake news in the citizen communication of the canton El Empalme sector San Felipe, because at this time the news spread faster in the digital age, through channels of dissemination in social networks and these contents in their vast majority are not identified as false by readers, for this in this study three methods were used the analytical, interpretive and descriptive, also a survey was applied as an instrument to obtain real information from the citizens of the sector, through the application of this methodology it was possible to know the preference of these people in terms of the social network that they mostly use to search for information, which of them consider that generates more false content, we also knew the frequency with which these individuals share information without first being analyzed and verified, thus verifying the consequences that produces the exposure of digital fake news in citizen communication, giving as effect alarm and confuse people through inaccurate information.